1937
DOI: 10.1021/ja01289a040
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Water and Hydrogen Peroxide at Low Pressures

Abstract: Vol. 59 hibit the same agreement in the PVT behavior of the ortho and para forms of the gas.A recently published paper by Schafer [Z. physik. Chem., 36, 85 (1937) ] describes a similar investigation of the data of state of normal and para hydrogen, his results agreeing very well with ours, although calculated differently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1939
1939
1968
1968

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Earlier work (16,14) has shown that both water and l~ydrogen peroxide are obtained a t liquid air temperatures but only water is obtained a t -78°C. In the present study, product yields were determined as a function of trapping temperature over the intervening range.…”
Section: Influence Of Trapping Temperaturementioning
confidence: 98%
See 3 more Smart Citations
“…Earlier work (16,14) has shown that both water and l~ydrogen peroxide are obtained a t liquid air temperatures but only water is obtained a t -78°C. In the present study, product yields were determined as a function of trapping temperature over the intervening range.…”
Section: Influence Of Trapping Temperaturementioning
confidence: 98%
“…Several mecha~lisms have been proposed (2,16,19) to explain the formation of these final products from the hydrogen atoms and hydroxyl radicals formed initially in the disAKanzcscript…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the early experiments of Geib and Harteck (31,32), and Rodebush and coworkers (33,34), show that when oxygen is added to a stream of hydrogen atoms or water vapor is dissociated in the discharge, other complex surface reactions occur which produce mainly H, and 0, at room temperature and H,O, at liquid N, temperatures. Foner and Hudson (35) have reported OH radicals coming from the surfacein the H-0, system at room temperature.…”
Section: Surface Reactionsmentioning
confidence: 99%